2018
DOI: 10.1139/cjfr-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Scots pine provenance affects the emission rate and chemical composition of volatile organic compounds of forest floor

Abstract: Scots pine (Pinus sylvestris L.) is an important source of biogenic volatile organic compounds (BVOCs) in the boreal zone. BVOC emission rate and profile affect air quality, climate forcing, plant stress tolerance, and thus the growing conditions of forests. BVOC emission profile of shoots and forest floor, as well as emission rates from forest floor, were studied in a latitudinal provenance experiment with 19-year-old Scots pine common garden in Central Finland. The provenances studied were Saaremaa (SAA, 58°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
3
14
1
Order By: Relevance
“…8). Similar total mean isoprenoid flux rates (28.9-81.5 μg m -2 h -1 ) were also measured from the Pinus sylvestris forest floor in the hemiboreal (Estonia coast) and boreal climates (northern Finland) (Kivimäenpää et al, 2018). Our results were supported by a previous study, where the monoterpene emission rate from decomposition of Pinus sylvestris litter was from five to nearly ten times higher than from decomposition of Picea abies litter within the first 77 days (Isidorov et al, 2010).…”
Section: Plant Ecophysiological Processes Affect Forest Floor Voc Excsupporting
confidence: 90%
“…8). Similar total mean isoprenoid flux rates (28.9-81.5 μg m -2 h -1 ) were also measured from the Pinus sylvestris forest floor in the hemiboreal (Estonia coast) and boreal climates (northern Finland) (Kivimäenpää et al, 2018). Our results were supported by a previous study, where the monoterpene emission rate from decomposition of Pinus sylvestris litter was from five to nearly ten times higher than from decomposition of Picea abies litter within the first 77 days (Isidorov et al, 2010).…”
Section: Plant Ecophysiological Processes Affect Forest Floor Voc Excsupporting
confidence: 90%
“…Pinus sylvestris is an important source of biogenic volatile organic compounds, which emission rate and profile affect air quality, climate forcing, plant stress tolerance, and thus the growing conditions of forests (Kivimäenpää et al, 2018). The reaction of P. sylvestris to various stress factors (low temperatures, industrial pollution, and action of fungi) showed changes in the content and composition of secondary metabolites (phenols, resins, essential oils).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some plant species such as woody shrubs (Himanen et al 2010;Mofikoya et al 2018) growing in the understory can act as significant emission sources. On the forest floor, important BVOC emission sources include leaf, needle and wood litter Mäki et al 2017;Kivimäenpää et al 2018) and the root systems of living (Lin et al 2007;Rasheed et al 2017) and dead trees (Haapanala et al 2012;Kivimäenpää et al 2012). BVOC synthesis and emissions by soil microbes in temperate and boreal forests still need similar assessment as in tropical forests (Bourtsoukidis et al 2018).…”
Section: Bvocs Of Rhizosphere Litter and Understorymentioning
confidence: 99%